Changes in interstitial cells and gastric excitability in a mouse model of sleeve gastrectomy. - Suk Bae Moon; Sung Jin Hwang; Sal Baker; Minkyung Kim; Kent Sasse; Sang Don Koh; Kenton M Sanders; Sean M Ward (PLoS ONE)
Obesity is a critical risk factor of several life-threatening diseases and the prevalence in adults has dramatically increased over the past ten years. In the USA the age-adjusted prevalence of obesity in adults was 42.4%, i.e., with a body mass index (BMI, weight (kg)/height (m)2) that exceeds 30 kg/m2. Obese individuals are at the higher risk of obesity-related diseases, co-morbid conditions, lower quality of life, and increased mortality more than those in the normal BMI range i.e., 18.5-24.9 kg/m2. Surgical treatment continues to be the most efficient and scientifically successful treatment for obese patients. Sleeve gastrectomy or vertical sleeve gastrectomy (VSG) is a relatively new gastric procedure to reduce body weight but is now the most popular bariatric operation. To date there have been few studies examining the changes in the cellular components and pacemaker activity that occur in the gastric wall following VSG and whether normal gastric activity recovers following VSG. In the present study we used a murine model to investigate the chronological changes of gastric excitability including electrophysiological, molecular and morphological changes in the gastric musculature following VSG. There is a significant disruption in specialized interstitial cells of Cajal in the gastric antrum following sleeve gastrectomy. This is associated with a loss of gastric pacemaker activity and post-junctional neuroeffector responses. Over a 4-month recovery period there was a gradual return in interstitial cells of Cajal networks, pacemaker activity and neural responses. These data describe for the first time the changes in gastric interstitial cells of Cajal networks, pacemaker activity and neuroeffector responses and the time-dependent recovery of ICC networks and normalization of motor activity and neural responses following VSG.